Implementasi Gaudium et Spes Art. 1 dalam Konteks Eklesiologi Keuskupan Agung Pontianak - Bernardus Putra, Gerwin; Denny Firmanto, Antonius; Wijiyati Aluwesia, Nanik (Borneo Review, 2022)
The Second Vatican Council has indeed renewed the Church and its relationship with the world. Gaudium et Spes is one of the many documents and constitutions that emerged from the Second Vatican Council. Ecclesiology After the Second Vatican Council experienced many positive developments. The problem formulations in this article are: 1) what is Gaudium et Spes and its context in Ecclesiology after the Second Vatican Council? 2) What is the external situation of the Pontianak Archdiocese Church after the Second Vatican Council? 3) How to implement Gaudium et Spes art. 1 in the Archdiocese of Pontianak? Then the purpose of this scientific work is to 1) describe Gaudium et Spes and its context in Ecclesiology after the Second Vatican Council, 2) describe the external situation of the Pontifical Archdiocese Church after the Second Vatican Council, and 3) describe efforts to implement Gaudium et Spes art. 1 in the Archdiocese of Pontianak. The method of writing this scientific paper is a literature study based on historical-critical and reflective analysis. The result of the research in this scientific work is that the Second Vatican Council sees the world in a more positive light. The world is seen as a whole human family with everything around it. Gaudium et Spes is the fruit of the Second Vatican Council. The situation of the Pontianak Archdiocese Church after the Second Vatican Council underwent many significant changes in various aspects. The Archdiocese of Pontianak implements the spirit of Gaudium et Spes art. 1 especially in the field of Education. STKIP Pamane Talino, Akper Dharma Insan, and Akbid St. Benedict is living proof of that implementation.